Determinants of approach behavior for ChatGPT and their configurational influence in the hospitality and tourism sector: A cumulative prospect theory - Han, H.; Seongseop (Sam), K.; Hailu, T. B.; Al-Ansi, A.; Loureiro, S. M. C.; Kim, J. J. (International Journal of Contemporary Hospitality Management, 2025)
Purpose This research paper aims to explore the concerns and determinants of travelers’ behavior toward ChatGPT in the hospitality and tourism context. It also examines the weight of risk factors versus that of motivation and innovation characteristics influencing travelers’ approach behaviors toward ChatGPT. Design/methodology/approach A cumulative prospect theory was used to determine travelers’ responses to ChatGPT. This study, using a fuzzy-set qualitative approach, explored risk, motivation and innovation factors as determinants of approach behaviors for ChatGPT. Findings Findings revealed that risk, motivation and innovation factors were the key triggers of approach behaviors for ChatGPT. An intricate combination effect of the perceived risk, motivation and innovation characteristics was found, and the necessary predictors were determined. Practical implications The findings of this study will expand our current knowledge and offer practical insights for the development of ChatGPT in the hospitality and tourism sector. Originality/value This study makes a significant contribution to the existing literature by providing a nuanced understanding of the intricate interplay between the various factors that shape customer behavior in the context of technology adoption in hospitality and tourism studies.